2011
DOI: 10.1128/aac.01201-10
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effects of Acidic pH on the Extracellular and Intracellular Activities of the Anti-Gram-Positive Fluoroquinolones Moxifloxacin and Delafloxacin againstStaphylococcus aureus

Abstract: In contrast to currently marketed fluoroquinolones, which are zwitterionic, delafloxacin is an investigational fluoroquinolone with an anionic character that is highly active against Gram-positive bacteria. We have examined the effect of acidic pH on its accumulation in Staphylococcus aureus and in human THP-1 cells, in parallel with its activity against extracellular and intracellular S. aureus. Moxifloxacin was used as a comparator. Delafloxacin showed MICs 3 to 5 log 2 dilutions lower than those of moxiflox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(152 citation statements)
references
References 45 publications
5
140
0
2
Order By: Relevance
“…Conversely, we can offer no explanation for moxifloxacin at this stage, as this will require more extensive studies and detailed comparisons with other fluoroquinolones and other strains. Notably, however, a biphasic shape was also observed when studying the intracellular activity of delafloxacin, a very potent investigational fluoroquinolone (30), against S. aureus. In this case, as in the present study, a biphasic response was observed when extending the range of concentrations to high multiples of the MIC (typically 1,000ϫ, which was possible for delafloxacin in view of its very low MICs, but explains why it escaped our attention in previous studies with other fluoroquinolones).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, we can offer no explanation for moxifloxacin at this stage, as this will require more extensive studies and detailed comparisons with other fluoroquinolones and other strains. Notably, however, a biphasic shape was also observed when studying the intracellular activity of delafloxacin, a very potent investigational fluoroquinolone (30), against S. aureus. In this case, as in the present study, a biphasic response was observed when extending the range of concentrations to high multiples of the MIC (typically 1,000ϫ, which was possible for delafloxacin in view of its very low MICs, but explains why it escaped our attention in previous studies with other fluoroquinolones).…”
Section: Discussionmentioning
confidence: 99%
“…Selection of resistance in S. aureus is infrequent (10 29 to 10 211 ), and concentrations preventing the selection of mutations (MPC (126)) range from 1 to 4 times the initial MIC, with values 8-to 32-fold lower than for other quinolones (127). Delafloxacin also proved active in in vitro models of biofilm or intracellular infection by S. aureus (124,128), despite the fact it mainly localizes in the cytoplasmic compartment of cells (124). This may be due to the high diffusibility of fluoroquinolones, which may help them freely to cross biological membranes within the cells to gain access to the infected compartment.…”
Section: Resultsmentioning
confidence: 99%
“…This chemical feature rationalizes why it accumulates much more in both bacteria and eukaryotic cells at acidic pH (124). Delafloxacin shows very low MICs against Gram-positive pathogens, with values typically 4 dilutions lower than those of moxifloxacin, even against strains showing elevated MIC to the reference drug (124). At acidic pH, the difference in potency between the two antibiotics can reach 7 dilutions (124).…”
Section: Resultsmentioning
confidence: 99%
“…: skin and soft tissue infections). This feature makes delafloxacin special among fluoroquinolones as ciprofloxacin and moxifloxacin lose potency in acidic environment [7,8]. Delafloxacin is a broad-spectrum agent, as it targets both DNA gyrase and topoisomerase IV enzymes [9].…”
Section: Commentarymentioning
confidence: 99%